Analisis Solusi Permasalahan Non-Performing Loan Di Koperasi Simpan Pinjam dan UMKM - Heriyaldi; Aurellia, Arfita; Shanaya, Nafsani; Widiandini Prita, Hapsari (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2020)
The bad credit or Non-performing Loan (NPL) in cooperative can be a problem that always happensevery year. With that, the government tries to reduce the NPL number as little as possible so the lossdoes not occur. This paper uses the primary data collection method, the writers interviewed the headof bank bukopin Cimahi’s branch and the writers also interviewed members of several cooperativesin Bandung and Jatinangor. The results of the interview stated that the problem of bad credit wascaused by, among others, members of the cooperative who had stalled in returning their loans, themanagement of the cooperative’s financial system was not good, and the business of the cooperativebeing undertaken is in decline. This certainly can result the distribution of credit through the linkageprogram being problematic.Seeing the problem of bad credit that occur, AKKI can be a solution fora strategy to strengthen MSME finance, especially in terms of capital. AKKI is an independentinstitution under the auspices of the Ministry of Cooperatives and Micro and Small and MediumEnterprise that integrates credit insurance throughout the Indonesian Cooperatives, so that eachcooperative can be insured to minimize the risk of dissolving a cooperative based on the reasons ofbad credit. This research is important to read as one of the efforts to realize financial stability incooperatives and MSMEs, especially in the sector of capital obtained from credit by reducing thenumber of Non-Performing Loans that continue to exist each year. With this, cooperatives canincrease their existence in Indonesia.